The Royal Mint Museum
The Royal Mint Museum contains a valuable numismatic library of some 15,000 volumes. This includes archival material acquired in large part from departments of the old Royal Mint at Tower Hill, such as the Engraving Department, the Die Office and the Pyx Office. For the most part this material dates back to the beginning of the 20th century and in its day-by-day character is a useful adjunct to the official files in The National Archives and to the published Annual Reports of the Royal Mint.

The National Farm Survey, 1941–1943: Collection highlights (The National Archives)
The National Farm Survey was created during the Second World War to increase food production and to plan for post-war agriculture.

British Library Sounds (The British Library)
Oral history. Interviews covering a wide range of subject areas related to British life and culture, including art, architecture, economics, social welfare, disability, music, sports, theatre, politics, photography, and more.
Keywords: _open access

British Pathé
Keywords: _open access